A Marketing authenticity and fair trade: toward a new relationship? Case of cooperatives in Souss Massa region - OUBOUTAIB, Fatima Ezzahra; MEKKAOUI , Soumiya; AITHEDA , Abdellatif (African Scientific Journal, 2021)
Abstract Fair trade has based on values such as trust, fairness, transparency and proximity, which are often displayed on the product’s packaging to meet the postmodern consumer’s need. This later asks for authenticity that rejoins the principles promoted by fair trade. Our paper is in line with this. It aims to explore the relationship between fair trade and authenticity through marketing approach. On the literature review’s section, we propose a state of the art on the marketing of authenticity and fair trade. Then, in the empirical section, we present a qualitative study with eight cooperatives in Souss Massa region on their practices and perceptions of this relationship. The key result is that despite the flowering of terroir products, the cooperatives display a certain ambiguity in their marketing’s manners. We advise cooperatives to consider this association: fair trade products and authenticity. Successful international trade would not always mean the marginalization of the local consumer: achieving international certification is a guarantee of quality, but satisfying local expectations is a guarantee of peripety. Keywords: marketing of authenticity, fair trade, authenticity, cooperative, Souss Massa